ORGANIZATIONAL AND ECONOMIC PRINCIPLES OF THE FUNCTIONING OF THE MILK MARKET UNDER THE CONDITIONS OF UKRAINE'S MEMBERSHIP IN THE EU - RADKO, Vitaliy; IBATULLIN, Marat; SVYNOUS, Ivan; SIRA, Yulia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the assessment of the organizational and economic basis of the functioning of the milk market in the conditions of Ukraine's membership in the EU. The main reasons for the reduction of the number of cows both in agricultural enterprises and households have been established. It has been proven that in the current conditions, the subjects of entrepreneurial activity - producers of dairy products do not have the opportunity to carry out even a simple reproduction of the cow population at the expense of their own sources. Today, the system of tribal service, which existed earlier in Ukraine and made it possible to conduct tribal affairs at the proper level, does not work. Therefore, further increase in productivity and improvement of animal reproduction indicators are extremely problematic due to the lack of a modern breeding system in animal husbandry.It has been established that most dairy farms have passed the stage of modernization of the material and technical base, which ensures the production of high-quality milk. In our opinion, subjects of entrepreneurial activity in the field of agro business - milk producers can compete with agricultural producers from EU countries in the presence of effective state support for dairy farming and the observance of partnership relations with processing enterprises and trade. The introduction of innovative technologies in dairy farming, especially agricultural enterprises, ensures a high level of milk productivity of cows, which corresponds to the corresponding values ​​of the average annual milk yield of most countries of the European Union.The analysis of benefits and risks for dairy farming from Ukraine's participation in the EU makes it possible to determine the directions of the national policy in terms of reducing risks, neutralizing negative consequences and accelerating the realization of benefits from the liberalization of trade regimes: promotion of exports with the aim of expanding foreign sales markets for Ukrainian exporters of dairy products; stimulation of domestic demand for milk and milk products; increasing the competitiveness of domestic producers of milk and milk products on the basis of improving the quality and safety of products due to the implementation of international quality standards; ensuring the competitiveness of domestic producers on domestic and foreign markets in accordance with effective state support measures for mixed agricultural enterprises - milk producers with the aim of attracting private investments for their development; avoiding negative impacts on personal peasant farms on the basis of the development of service and sales cooperation, the formation of the appropriate infrastructure, financial support for the process of transformation of commercial personal peasant farms into small agribusiness subjects - milk producers; promotion of rural development, active use of the benefits of the "green box" by the World Trade Organization.
Keywords: dairy farming; EU; agricultural enterprise; household economy; state support